2006
DOI: 10.1136/thx.2005.051292
|View full text |Cite
|
Sign up to set email alerts
|

Adding salmeterol to an inhaled corticosteroid: long term effects on bronchial inflammation in asthma

Abstract: Background: Addition of the long acting b 2 agonist salmeterol to inhaled corticosteroids leads to better symptomatic asthma control than increasing the dose of inhaled corticosteroids. However, little is known about the long term effects of adding salmeterol on the asthmatic inflammatory process, control of which is considered important for the long term outcome of asthma. Methods: After a 4 week fluticasone run-in period, 54 patients with allergic asthma were randomised to receive twice daily treatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…Moreover, improvements in lung function, symptom scores and bronchial hyper-responsiveness following inhaled fluticasone (500 μg daily) in combination with salmeterol (100 μg daily) treatment were associated with changes in sputum α2 macroglobulin and albumin rather than in sputum cell counts [131] and also reduced serum IL-5 and peripheral blood eosinophil numbers [132].…”
Section: Moderate Persistent Asthmamentioning
confidence: 98%
“…Moreover, improvements in lung function, symptom scores and bronchial hyper-responsiveness following inhaled fluticasone (500 μg daily) in combination with salmeterol (100 μg daily) treatment were associated with changes in sputum α2 macroglobulin and albumin rather than in sputum cell counts [131] and also reduced serum IL-5 and peripheral blood eosinophil numbers [132].…”
Section: Moderate Persistent Asthmamentioning
confidence: 98%
“…[233][234][235][236][237][238] The trials were published between 1999 and 2006 ( Table 55). Four were multi-centre studies and two single-centre studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Four were multi-centre studies and two single-centre studies. Sample sizes were 54 and 282 in the two single-centre studies 236,237 and ranged between 349 and 3421 participants in the multi-centre studies. All but one trial 233 reported that a power calculation was undertaken and sample sizes suggest that adequate power was met.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations